2017
DOI: 10.1158/1078-0432.ccr-16-1501
|View full text |Cite
|
Sign up to set email alerts
|

Active Estrogen Receptor-alpha Signaling in Ovarian Cancer Models and Clinical Specimens

Abstract: Purpose High-grade serous ovarian cancer (HGSOC) is an aggressive disease with few available targeted therapies. Despite high expression of estrogen receptor-alpha in ~80% of HGSOC and some small but promising clinical trials of endocrine therapy, estrogen receptor-alpha has been understudied as a target in this disease. We sought to identify hormone-responsive, estrogen receptor-alpha-dependent HGSOC. Experimental Design We characterized endocrine response in HGSOC cells across culture conditions (2-D, 3-D,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 45 publications
5
41
0
Order By: Relevance
“…Our data showed that estrogen metabolism did not correlate with ESR1, ESR2, and ESRRG expression. This is supported by a previous paper by Andersen et al [48], showing that approximately 80% of HGSOC tumor samples express ESR1; however, the response to an antiestrogenic therapy in patients is rather poor. This group also reported that the ERα status in HGSOC cells is not a sufficient tool to predict the response to an antiestrogenic therapy.…”
Section: Discussionsupporting
confidence: 78%
“…Our data showed that estrogen metabolism did not correlate with ESR1, ESR2, and ESRRG expression. This is supported by a previous paper by Andersen et al [48], showing that approximately 80% of HGSOC tumor samples express ESR1; however, the response to an antiestrogenic therapy in patients is rather poor. This group also reported that the ERα status in HGSOC cells is not a sufficient tool to predict the response to an antiestrogenic therapy.…”
Section: Discussionsupporting
confidence: 78%
“…For example, epidemiological studies found that women treated with hormone replacement therapy had an increased risk of ovarian cancer . However, antiestrogen therapy was only somewhat effective for a subset of ovarian cancer patients, regardless of ER‐α expression status …”
Section: Discussionmentioning
confidence: 99%
“…[ 12a ] It is an effective strategy that the precise oncology models corroborate intertumor heterogeneity to identify the key genes closely associated with clinical response. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%